2019
DOI: 10.1039/c9cp02663k
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the role of redox-active materials during laser-induced water decomposition

Abstract: The decomposition of water and the formation of molecular hydrogen, oxygen, and hydrogen peroxide during laser ablation of redox-active materials is systematically studied and related to the ablation rate and oxidation degree of the nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 86 publications
2
81
0
Order By: Relevance
“…A closer look to the spectra reveals slight differences after laser irradiation, as a higher absorption of the C–O peak at 1060 cm −1 and the C–H peaks at 2860 cm −1 and 1470 cm −1 . This fact indicates the increased presence of C–OH and CH 2 surface groups, which can be explained due to the higher surface area after particle size reduction and the generation of molecular O and H based radicals or molecules from water splitting during laser irradiation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…A closer look to the spectra reveals slight differences after laser irradiation, as a higher absorption of the C–O peak at 1060 cm −1 and the C–H peaks at 2860 cm −1 and 1470 cm −1 . This fact indicates the increased presence of C–OH and CH 2 surface groups, which can be explained due to the higher surface area after particle size reduction and the generation of molecular O and H based radicals or molecules from water splitting during laser irradiation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the ablation of the Pt 0.66 Pd 0.33 target, the same trend in the productivity of total mass as well as the catalytically relevant nanoparticle size fraction below 10 nm was found ( Figure S2 ). Interestingly, when comparing the maximal ablation rate for Pt and Pt 0.66 Pd 0.33 , the ablation rate correlates with the material density [ 61 ] so that a similar volume-related ablation rate of about 0.27 cm³/h was found for both (see Figure 2 and Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The redox chemistry between the target material and water affects not only the NP productivity during long‐term ablation but also the oxidation degree of the final NPs, as also theoretically predicted by Reichenberger et al. based on Nernst equation and correlated to experimental findings [35, 62, 63] However, all these experiments were performed for multi‐pulse laser ablation with repetition rates in the kHz regime. Hence, cavitation bubbles, [16, 17] persistent bubbles [60–63] or NPs [61–63, 68–70] formed during LAL induce cross‐effects.…”
Section: Introductionmentioning
confidence: 85%
“…However, the time regime of the rebound/collapse of the bubble must also be considered but is often neglected as most studies focus on the primary cavitation bubble cycle. Within this context, several studies have demonstrated that water is decomposed during LAL resulting in the formation of molecular hydrogen, oxygen, and hydrogen peroxide [60–67] . The individual formation rates of these decomposition products depend strongly on the type of the ablated material.…”
Section: Introductionmentioning
confidence: 99%